2005
DOI: 10.1182/blood-2004-09-3515
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pathogenic SHIV replication in macaques treated with antisense DNA of interleukin-4

Abstract: IntroductionThe pathogenesis of HIV infection and the complex disease patterns caused by the virus are known to revolve around the dystrophic effects of the infection first, in helper CD4 ϩ T cells, and later in cells of the macrophage lineage in organs such as the lungs, spleen, and brain. [1][2][3][4][5][6] Loss of virus-infected CD4 ϩ T cells heralds the loss of interferon-␥ (IFN-␥)-mediated T-cell responses, and this creates an environment favorable for productive replication of opportunistic pathogens. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…IL-4 and IL-13 expression has been found to be present in the normal brain (Szczepanik et al 2001), and IL-4 has been found to have a role in the CNS and other pathologies induced by SHIV infection in macaques (Buch et al 2004;Dhillon et al 2005). The cellular sources of IL-4 and IL-13 in the brain, however, are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 and IL-13 expression has been found to be present in the normal brain (Szczepanik et al 2001), and IL-4 has been found to have a role in the CNS and other pathologies induced by SHIV infection in macaques (Buch et al 2004;Dhillon et al 2005). The cellular sources of IL-4 and IL-13 in the brain, however, are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (10,28) have suggested that Th2-inducing parasite infestations enhance lentiviral production at local sites. Work in our labo- ratory had indicated that the IL-4 and the chemokine, MCP-1, selectively enhanced replication of CXCR4-utilizing viruses (11,13,33). Other studies have confirmed the importance of these cytokines in supporting SIV (7) and HIV replication (18,19,32,37).…”
Section: Discussionmentioning
confidence: 67%
“…The dramatic effect of host factors on replication of the virus was identified in our subsequent studies. In previous reports, we (26,33) have shown that monocyte chemotactic protein-1 (MCP-1), CXC chemokine ligand 10 (CXCL10), interleukin-4 (IL-4), and platelet-derived growth factor (PDGF) caused enhancement of viral replication in macrophages, and these cytokines were found in abundance in inflamed virus-infected lungs of macaques (8,11,33).…”
Section: Pneumonia Is a Major Complication Of Human Immunodeficiency mentioning
confidence: 99%
See 2 more Smart Citations